Performance of τ-lepton reconstruction and identification in CMS - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
The performance of τ-lepton reconstruction and identification algorithms is studied using a data sample of proton-proton collisions at s = 7 TeV, corresponding to an integrated luminosity of 36 pb-1 collected with the CMS detector at the LHC. The τ leptons that decay into one or three charged hadrons, zero or more short-lived neutral hadrons, and a neutrino are identified using final-state particles reconstructed in the CMS tracker and electromagnetic calorimeter. The reconstruction efficiency of the algorithms is measured using τ leptons produced in Z-boson decays. The τ-lepton misidentification rates for jets and electrons are determined. © 2012 CERN for the benefit of the CMS collaboration, published under license by IOP Publishing Ltd and SISSA.